Majority-Minority Relations in Contemporary Women's Movements - Predelli, L. author. aut Link
XVI, 335 p.
Keywords: This book examines contemporary relations between ethnic majority and ethnic minority women's movements in Norway, Spain and the United Kingdom, and women's movements' participation in and influence on public policy that focuses on violence against women.